Retraction Statement: Comparison of nitrogen inputs and accumulation in 210Pb‐dated peat cores: Evidence for biological N2‐fixation in Central European peatlands despite decades of atmospheric N pollution. (25th November 2018) - Novak, Martin; Vile, Melanie A.; Curik, Jan; Cejkova, Bohuslava; Barta, Jiri; Stepanova, Marketa; Jackova, Ivana; Buzek, Frantisek; Bohdalkova, Leona; Prechova, Eva; Veselovsky, Frantisek; Adamova, Marie; et al.
Abstract : "Comparison of nitrogen inputs and accumulation in 210 Pb‐dated peat cores: Evidence for biological N 2 ‐fixation in Central European peatlands despite decades of atmospheric N pollution" https://doi.org/10.1111/gcb.14505, by Martin Novak, Melanie A. Vile, Jan Curik, Bohuslava Cejkova, Jiri Barta, Marketa Stepanova, Ivana Jackova, Frantisek Buzek, Leona Bohdalkova, Eva Prechova, Frantisek Veselovsky, Marie Adamova, Ivana Valkova and Arnost Komarek . The above article, first published online in Wiley Online Library (wileyonlinelibrary.com) in Global Change Biology, has been retracted by agreement between the authors, the journal Editor‐in‐Chief, Stephen P. Long, and John Wiley & Sons Ltd. Since publication of the above article, it was brought to the attention of the authors that the peat accretion rates violate reasonable ranges of peatland C/N/P stoichiometry, placing the quantitative conclusions of the article in serious error. The authors apologize for any inconvenience the publication of this work may have caused our readers. REFERENCE Novak, M., Vile, M. A., Cejkova, B., Barta, J., Stepanova, M., Jackova, I., Buzek, F., Bohdalkova, L., Prechova, E., Veselovsky, F., Adamova, M., Valkova, I., & Komarek, A. (2018). Comparison of nitrogen inputs and accumulation in 210 Pb‐dated peat cores: Evidence for biological N2 ‐fixation in Central European peatlands despite decades of atmospheric N pollution. Global Change Biology .. https://doi.org/10.1111/gcb.14505